School Policies in Fostering Students’ Character through Base Krame Cultural Practices - Hafizi, Ahmad Yusron (Pendidikan Agama Islam STIT Palapa Nusantara, 2026)
This study is motivated by the limited empirical research on the practical integration of Islamic values and local cultural wisdom in public elementary schools, despite its relevance to character education within contemporary curriculum reform. It aims to analyze how school policies integrate Islamic values grounded in base krame cultural practices to foster students’ character in the context of the Merdeka Curriculum and digital learning. The study employed a qualitative design at SDN Pemantek, Prako Village, Janapria District, Central Lombok, involving 25 purposively selected participants consisting of school leaders, teachers, students, parents, and community figures. Data were collected through in-depth interviews, observations, and document analysis, and analyzed using an interactive qualitative analysis model comprising data condensation, data display, and conclusion drawing and verification. The findings indicate that character education is institutionalized as a lived moral culture in which Islamic ethics provide spiritual foundations, while base krame embodies norms of politeness, respect, and social responsibility. Teacher role modeling, daily habituation practices, and school-family-community collaboration function as the primary mechanisms of value internalization. The study also finds that digitalization is addressed through ethical adaptation, with base krame values guiding respectful online communication. The study concludes that culturally grounded and spiritually integrated school policies effectively support holistic character formation. These findings contribute to the development of integrative character education and offer practical implications for schools and policymakers seeking to align curriculum reform with local ethical frameworks.